The Effect of the Application of the Make-a-Match Model on the Ability to Understand Mathematical Concepts and Student Learning Activity - Riska Rahayu; Adelia Azzahra; Hendri Handoko; Muslihudin Muslihudin; Nur Saebah (International Journal of Social Service and Research, 2023)
This study aims to evaluate the impact of the Make a Match learning model on the ability to understand mathematical concepts, student learning activity, and their response to mathematics learning. The research method used is a quantitative approach with a quasi-experimental design using the nonequivalent group posttest only design method. Data collection techniques involve tests, questionnaires, and documentation. The research sample consisted of class VIII E students as the experimental group and class VIII B as the control group, with a total of 34 students. Research findings show that: 1) the application of the Make a Match learning model has a significant positive impact on the ability to understand mathematical concepts, with an influence of 53.7%, 2) there is a significant influence on student learning activity with the application of the Make a Match learning model, with an influence of 23.4%, and 3) student response to learning using the Make a Match model reaches 87.50%,  with good category. These results contribute positively to the understanding of mathematical concepts, learning activity, and student responses to the Make a Match learning model.